Distribution of microplastics in mulched soil in Xinjiang, China - Hu, Can; Lu, Bing; Guo, Wensong; Tang, Xiuying; Wang, Xufeng; Xue, Yinghao; Wang, Long; He, Xiaowei (International Journal of Agricultural and Biological Engineering, 2021)
In order to study the distribution of soil microplastics in the plastic film mulched farmland, the fluidization-centrifugation secondary density flotation method was optimized and improved to obtain the samples. The main components of microplastics were analyzed by Fourier spectrometer, and the surface morphology, porosity, particle size and abundance distribution characteristics of microplastics were studied by electron microscopy. The results showed that plastic mulch is the main source of microplastics. Its morphology mainly consists of fragments, fibers and particles. The size of debris microplastics was larger, with an average of 1.6300 mm, mainly distributed in the 0-300 mm cultivation layer while the size of particle micro plastic was smaller, with an average of 0.1400 mm. The width of fiber microplastic was 5-20 μm, but the length could reach 0.2000-2.0000 mm, with an average particle size of 0.9200 mm. Fiber and granular microplastics could be seen in each soil layer. The surface layer of microplastics has a large number of pores characterized with a length of 50 μm and a width of about 5-10 μm, which might be an easy oxidation site for microplastics. This oxidation is continuous, making microplastics continuously decompose into smaller particles. The abundance of microplastics is negatively correlated with soil depth. The average abundance of microplastics is 161.50±5.20 pieces/100 g in 0-300 mm soil layer, which is their main enrichment area. However, the average abundance of microplastics decreases to 11.20±1.10 pieces/100 g in 400-800 mm soil depth. Moreover, the average particle size of microplastics is also linearly negatively correlated with soil depth. Microplastics with smaller particle size are easier to migrate as they pass through soil pores under the action of water and fertilizer. The research can provide s reference for understanding plastic mulch pollution. Keywords: soil microplastics, plastic pollution, distribution, composition DOI: 10.25165/j.ijabe.20211402.6165 Citation: Hu C, Lu B, Guo W S, Tang X Y, Wang X F, Xue Y H, et al. Distribution of microplastics in mulched soil in Xinjiang, China. Int J Agric & Biol Eng, 2021; 14(2): 196–204.